Aerodynamic optimization of a truck bumper - Ceres, Umar (Stellenbosch : Stellenbosch University, 2025)
Ceres, U. 2025. Aerodynamic Optimization of a Truck Bumper. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/5035a627-642c-427d-9714-d08ee945d167